2013
DOI: 10.1016/j.jinsphys.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti pharate 1st instar quiescence: A case for anticipatory reproductive plasticity

Abstract: Aedes aegypti mosquitoes use pharate 1st instar quiescence to cope with fluctuations in water availability hosting a fully developed 1st instar larvae within the chorion. The duration of this quiescence has been shown to affect larval fitness. This study s ought to determine if an extended egg quiescence can elicit a plastic response resulting in an adult phenotype distinct from adults reared from short quiescence eggs. Our findings indicate that extended pharate 1st quiescence affects the performance and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
(51 reference statements)
1
14
0
4
Order By: Relevance
“…Maternal reserves accumulated in eggs directly influence the period of dormancy in the first-instar larvae contained within the eggs [8, 120]. Thus, quiescent eggs pose an important problem for vector control because these eggs can directly contribute to the maintenance of mosquito populations in treated areas.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal reserves accumulated in eggs directly influence the period of dormancy in the first-instar larvae contained within the eggs [8, 120]. Thus, quiescent eggs pose an important problem for vector control because these eggs can directly contribute to the maintenance of mosquito populations in treated areas.…”
Section: Introductionmentioning
confidence: 99%
“…Hatch timing may influence other traits such as insecticide resistance and fitness. Recently Perez and Noriega [38] showed that extended quiescence (eggs induced to hatch after 10 weeks post oviposition instead of after just less than one week for short quiescence) affected performance and reproductive fitness of adult Aedes aegypti females and the nutritional status of their progeny via maternal effect. Specifically, the females from the eggs that underwent extended quiescence survived 10% longer, laid more eggs and produced 14% more viable offspring when reared on a sub-optimal diet of 3% sucrose solution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we can envisage two opposite scenarios. In the first, because metabolic rates increase with temperature (Gillooly et al, 2001) and lead to higher energy consumption before the return of favourable conditions (Williams et al, 2012;Xiao et al, 2016), maintaining relatively high metabolic rates during diapause or extended quiescence under a warmer climate would be costly (Perez & Noriega, 2013). Accordingly, the capacity to delay, avert, or reduce diapause duration may be selected in insect populations (Bale & Hayward, 2010), especially when overwintering conditions allow individuals to remain active and reproduce (Forrest, 2016).…”
Section: Decrease In Winter Cold Severitymentioning
confidence: 99%